Awareness of Cancer Symptoms and Barriers to Seeking Medical Help Among Adult People Attending Primary Care Settings in Oman. (25th October 2016) - Al-Azri, Mohammed; Al-Maskari, Aziza; Al-Matroushi, Salma; Al-Awisi, Huda; Davidson, Robin; Panchatcharam, Sathiya Murthi; Al-Maniri, Abdullah
Objectives: To explore the public's awareness of cancer symptoms and the barriers to seeking medical help among Omani adults attending primary care settings in Muscat governorate, the capital city of Oman. Methods: The Cancer Awareness Measure (CAM) questionnaire (translated into Arabic) was used to collect data from a total of 12 randomly selected local health centers (LHCs) in Muscat governorate, the capital city of Oman. Omani adults aged 18 years and above attending LHCs during the study period were invited to participate in the study. Statistical Package for the Social Sciences (SPSS version 22) was used to analyze the data. Results: A total of 999 participants completed the CAM questionnaire from 1200 invitations (response rate = 83%). The overall recognition of common cancer symptoms was less than 50% except for an unexplained lump/swelling, which was 71%. Multinomial logistic regression showed that women recognized more cancer symptoms than men (odds ratio [OR] = 1.79; 95% confidence interval [CI]: 1.27-2.51), that more highly educated participations recognized more cancer symptoms than less educated participants (OR = 39; 95% CI: 0.23-0.69). The majority of participants (91.2%) agreed that the right time to seek medical help for possible cancer symptom was within 2 weeks. Multinomial logistic regression showed that women rather than men were more likely to perceive barriers to seeking medical help (OR = 2.10; 95% CI: 1.60-2.76). Also the less educated participants, rather than more educated, were more likely to perceive barriers to seeking medical help (OR = 2.17; 95% CI: 1.16-4.05). Conclusion: Levels of awareness of cancer symptoms are low in Oman. More national CAMs are needed in Oman to increase public knowledge of cancer symptoms. Also, more public awareness is needed to overcome the barriers to seeking timely medical help particularly among groups of women and the unmarried, widowed, divorced, or separated if delays in presentation are to be minimized.